Geoprocessamento integrado à modelagem hidrológica para o diagnóstico ambiental e a qualificação de cenários de uso e perda de solo na bacia hidrográfica do Rio Vitorino - PR - Vottri, Marciano (2018)
Sustainable development aims at equitably encompass three elements: social, environmental and economic, with the central objective of meeting the needs of today's society without compromising the lives of future generations. Soil erosion due to water action and sedimentation to water courses has been aggravated by incompatible use, management and occupation, favoring the occurrence of serious environmental, social and economic impacts. In this context, the research aimed to perform the social environmental diagnosis of the Vitorino River Basin PR (BHRV), analyzing the influence of the variation of land use and occupation related to soil losses. The results were obtained from the integrated analysis of the main environmental indicators related to soil degradation processes due to erosion associated with geoprocessing and hydrological modeling presented through thematic maps. The research showed that the current model of agricultural production presents weaknesses in soil conservation. The socioenvironmental and perception analysis pointed to a direct correlation to the environmental liabilities but insufficient to impose an alteration of man's behavior in relation to the problems exposed. The pedological, geographic and soil use and occupation characteristics showed a high influence on the erosive processes, directly influencing the surface runoff and sediment production according to their variations. The hydrosedimentological diagnosis showed soil losses varying from 3.86 to 42.71 t / ha / year, for the current use, while for the projected scenario the variation was 1.26 to 12.45 t / ha / year and average soil loss rates from 18.72 to 6.45 ton / ha / year of current use for the projected scenario. Despite the scarcity of input data and the fact that it is a non-instrumented hydrographic basin, geoprocessing associated with hydrological modeling has demonstrated a high capacity to generate information for environmental management. Therefore, the approach of the landscape under the dynamics of hydrographic basins in an integrated and systemic way to the anthropic occupation allowed to indicate that the applied methodology is of paramount importance to guarantee the preservation and conservation of the diverse ecosystems, providing activities that compact with the long term sustainability.